Cocopeat as Soil Substitute Media for Rubber (Hevea brasiliensis Müll. Arg.) Planting Material - Cahyo, Andi Nur; Sahuri, Sahuri; Nugraha, Iman Satra; Ardika, Risal (Journal of Tropical Crop Science, 2019)
To establish rubber plantations smallholders in South Sumatra, Indonesia, plant materials are planted in polybags fi lled with top soil media from the local area. Good quality media is very important to ensure optimal growth of the rubber planting materials. The availability of top soil has become increasingly limited. In order to fulfi ll the need of planting media, cocopeat, which is available in abundance in the area, can potentially be an alternative to top soil. Cocopeat can potentially be used alone, or in combination with other type of media. In this study, cocopeat was mixed with soil at several mixture ratios to determine the best formula of cocopeat based planting media for rubber planting material. The study was conducted from August 2016 to January 2017 in the Nursery of Sembawa Research Centre Experimental Field, Palembang, South Sumatra, Indonesia. A completely randomized design was employed with six combinations of cocopeat and soil, replicated three times. This study showed that the best mixture ratio is 80% cocopeat and 20% soil, whereas 100% soil or 100% cocopeat is not recommended. The use of cocopeat as planting media should be followed by balanced fertilization in order to provide nutrients that are not available in cocopeat.